EROSI KEDAULATAN DATA INDONESIA DALAM KAPITALISME DIGITAL GLOBAL: REKONSTRUKSI HUKUM TELEMATIKA - Dion Ario; Swandi Aliverchan Situngkir; Ricky Indawan Safutra; Demitha Selvira Amellia; Rahmatullah Ayu Hasmiati (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study examines the erosion of Indonesia’s data sovereignty within the structure of global digital capitalism and its implications for the reconstruction of telematics law. The issue is significant because the rapid expansion of transnational digital platforms has generated a structural imbalance between the State’s formal regulatory authority and its substantive control over data governance, thereby challenging Indonesia’s digital sovereignty and legal capacity in governing cyberspace. This study aims to analyze the structural factors contributing to the erosion of Indonesia’s data sovereignty and to formulate an adaptive reconstruction model of telematics law capable of responding to the dynamics of global digital capitalism. This research employs doctrinal legal research using statutory and conceptual approaches. The findings reveal a structural paradox: although Indonesia has strengthened its legal framework through data protection and digital governance regulations, substantive control over data flows, digital infrastructure, and algorithmic governance remains largely concentrated in transnational digital platforms. This paradox constitutes the principal finding and scientific contribution of the study, demonstrating that data sovereignty should be understood not merely as territorial legal authority but as a relational form of power within the architecture of platform capitalism. The novelty of this research lies in the formulation of an adaptive telematics law reconstruction model founded upon three interconnected principles: the expansion of digital jurisdiction, the strengthening of national digital infrastructure sovereignty, and enhanced platform accountability. Accordingly, this study concludes that strengthening Indonesia’s data sovereignty requires a shift from a regulatory-oriented approach toward a governance model capable of addressing structural asymmetries in the global digital ecosystem. Future research is encouraged to examine the operational effectiveness of this reconstruction model through comparative and empirical studies across different jurisdictions.